Effects of Conjugation with Basil Seed Gum on Physicochemical, Functional, Foaming, and Emulsifying Properties of Albumin, Whey Protein Isolate and Soy Protein Isolate - Hadi Hashemi; Mohammad Hadi Eskandari; Mohammadreza Khalesi; Mohammad-Taghi Golmakani; Mehrdad Niakousari; Seyed Mohammad Hashem Hosseini (Foods)
Protein conjugation with the Maillard reaction has received considerable attention in the past decades in terms of improving functional properties. This study evaluated the changes in the techno-functional properties of whey protein isolate (WPI), soy protein isolate (SPI), and albumin (Alb) after conjugation with basil seed gum (BSG). The conjugates were developed via the Maillard reaction. Various analyses including FT-IR, XRD, SEM, SDS-PAGE, DSC, RVA, rheology, zeta potential, emulsion, and foaming ability were used for evaluating conjugation products. Conjugation between proteins (WPI, SPI, Alb) and BSG was validated by FT-IR spectroscopy. XRD results revealed a decrease in the peak of BSG after conjugation with proteins. SDS-PAGE demonstrated the conjugation of WPI, SPI, and Alb with BSG. DSC results showed that conjugation with BSG reduced the Tg of WPI, SPI, and Alb from 210.21, 207.21, and 210.90 °C to 190.30, 192.91, and 196.66 °C, respectively. The emulsion activity and emulsion stability of protein/BSG conjugates were increased significantly. The droplet size of emulsion samples ranged from 112.1 to 239.3 nm on day 3. Nanoemulsions stabilized by Alb/BSG conjugate had the smallest droplet sizes (112.1 and 143.3 nm after 3 and 17 days, respectively). The foaming capacity of WPI (78.57%), SPI (61.91%), and Alb (71.43%) in their mixtures with BSG increased to 107.14%, 85.71%, and 85.71%, respectively, after making conjugates with BSG. The foam stability of WPI (39.34%), SPI (61.57%), and Alb (53.37%) in their mixtures with BSG (non-conjugated condition) increased to 77.86%, 77.91%, and 72.32%, respectively, after formation of conjugates with BSG. Conjugation of BSG to proteins can improve the BSG applications as a multifunctional stabilizer in pharmaceutical and food industries.